Alkoxy Group-Boosted Internal Redox Reaction: Application to Benzylic Hydride Shift/Cyclization of Electron-Deficient Aromatic Rings - Katagiri, Mizuki; Kawasaki-Takasuka, Tomoko; Mori, Keiji (Synlett, 2025)
We report a C(sp3)–H bond functionalization at the benzylic position of electron-deficient aromatic rings, considered a challenging transformation in hydride shift–mediated C(sp3)–H bond functionalization chemistry. The key to achieving the reaction was the employment of substrates having a methoxy group at the benzylic position. The methoxy group was easily eliminated from the cyclized adducts by treating with a strong Brønsted acid, such as TfOH. A one-pot operation of two processes, C(sp3)–H bond functionalization and MeOH elimination, was also accomplished. Synthetic utility of the present method was well showcased by derivatization from the obtained dihydronaphthalenes.
Keywords: C–H bond functionalization; Redox process; Tetralin; Hydride shift; Sequential reaction